HUKUM BERPUASA DALAM KONDISI PANDEMI COVID-19 - Gampang Dadiyono; Marzuki Umar (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
This research was conducted with the aim to explain the law of fasting during the Covid-19 pandemic upon those who are Covid-19 positive, those who were Covid-19 positive yet asymptomatic, and health workers who treat Covid-19 patients. This research used a qualitative approach using content analysis and library research. The results showed that, first, people who are Covid-19 positive are considered sick so that they have excuse to break the fasting; Second, those who are Covid-19 positive but show no symptoms are considered sick people so that they may not fast; Third, those who are still healthy and have not been infected with Covid-19 and have met the conditions of fasting and have no excuse that prevent them from fasting then it is obligatory upon them to fast; Fourth, medical workers who treat Covid-19 patients are still required to fast. If in conducting their duties they are very thirsty, hungry, or exhausted who are feared to be vulnerable to falling ill and be infected with Covid-19, then they may break their fast.